Systematic review and classification of: Coping Cat program - Haugland, Bente Storm Mowatt; Bjaastad, Jon Fauskanger (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2017)
This is not the most recent article on this program. Updated article: https://doi.org/10.7557/25.6688 Background: This article is a summary of current knowledge of the effects of “Mestringskatten” and “Mestringskatten for ungdom”, the Norwegian translation and adaptation of the American Coping Cat program (child version) and the C.A.T. project (adolescent version), respectively. The article is a revision of a review of Mestringskatten that was published previously in Ungsinn (Bratt, 2010). This summary has been revised to conform to the new scoring criteria and procedures for Ungsinn (Martinussen et al., 2016). Mestringskatten (7 – 13 years) and Mestringskatten for ungdom (14 – 17 years) are structured, manualized Cognitive Behavioral Therapy (CBT) programs. The child version is comprised of 12 sessions and the adolescent version of 14 youth sessions. Both versions include two additional sessions for parents. The target groups are children and adolescents with three types of anxiety: separation anxiety disorder, social anxiety disorder, and/or generalized anxiety disorder. The program is comprised of therapist manuals and separate workbooks for children and adolescents. Universitetsforlaget (www.universitetsforlaget.no) is the purveyor of the program in Norway. The purpose of this article is to examine whether the child and youth versions of Mestringskatten are effective when used in ordinary practice in Norway. Method: The following databases were searched to find articles about the intervention: Mbase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS, SweMed, Kunnskapssenteret, NREPP, NICE, Blueprints, and CEBC. In addition, information about the program from those responsible for the Norwegian translation and implementation of the program was obtained. Results: The intervention is very well described in manuals and workbooks. Mestringskatten and Mestringskatten for ungdom have good theoretical and empirical basis within the field of CBT. The effect of the original American child version of the program (Coping Cat) has been documented through many efficacy studies as well as in reviews and meta-studies. A Norwegian RCT effectiveness study has been conducted and registered in ClinicalTrials.gov. However, the results have not been published yet. Thus, the results and the scientific rigor of this study cannot be evaluated in this review. A two-day voluntary training workshop in Mestringskatten is available and supervision can be arranged. Besides this, there are no systems to ensure implementation quality of the program, indicating uncertainty as to how the program is used in clinical practice in Norway. Conclusion: Mestringskatten and Mestringskatten for ungdom are well described programs with a good theoretical foundation. Numerous, well-performed international effect studies and meta-studies confirm the effectiveness of the American version of the program for children (the Coping Cat), with less documentation with regard to the adolescent version (the CAT project). Although a Norwegian study has been conducted, effects of the program have not been published, and systems to ensure adequate implementation quality have not been developed. Based on Ungsinn’s criteria Mestringskatten applied in usual practice in Norway was classified at level 3: interventions with some documentation of effect.